Molecular identification and phylogenetic analysis of Bothrops insularis bacterial and fungal microbiota - Barbosa, Lidiane Nunes [UNESP]; Ferreira, Rui Seabra [UNESP]; Luiza Mello, Priscila [UNESP]; Garcia Garces, Hans [UNESP]; Luana Chechi, Jéssica [UNESP]; Frachin, Tarsila [UNESP]; De Barros, Luciana Curtolo [UNESP]; De Moraes Guimenes Bosco, Sandra [UNESP]; Bagagli, Eduardo [UNESP]; Fernandes Júnior, Ary [UNESP]; Barraviera, Benedito [UNESP]; Delazari Dos Santos, Lucilene [UNESP] (Taylor & Francis, 2018)
Bothrops insularis, known as the golden lancehead snake, has its natural habitat restricted to Queimada Grande Island on the southern coast of Brazil. This culture-dependent study aimed to identify microorganisms obtained from the mouth, eyes, and cloaca of this species. Swabs from 20 snakes were collected for fungal and bacterial isolation. DNA was extracted from all samples, and identification was performed by amplifying the ITS1-5.8S-ITS2 regions and the 16S rDNA gene, respectively. All strains were identified and deposited in the GenBank nucleotide database. MEGA v6.0 software was utilized to construct phylogenetic trees. In total, 100 strains were isolated and characterized, from which 42 fungi were distributed into 23 species and 58 bacteria into 13 species. The genus Fusarium was predominant since 11 strains and probably a new species was isolated from this fungus. Pseudomonas aeruginosa and Enterococcus faecalis were the predominant groups of aerobic bacteria isolated. Phylogenetic analyses between bacterial and fungal sequences suggest a similarity between the microorganisms found on the island and on the continent. These findings may be attributed to anthropic actions resulting from both expeditions to the island and actions of migratory birds, which are the main sources of food for snakes.